Cigarette, alcohol and substance use frequency among high school students: nevşehir sample - Özcan, Ayşegül; Küçük Öztürk, Gülhan; Özdil, Kamuran; Şermet Kaya, Şenay (Journal of Dependence, 2016)
Objective: Puberty that occurs changes in and has potential for developmental crisis is a risky period in terms of adolescents’ curiosity about looking for new and trying to different lives. This study was conducted to determine the frequency of smoking, alcohol-substance use among high school students in Nevşehir city. Method: This descriptive study was conducted between 2013-2014 school year. The population of the study was consisted from 8773 students at high schools in Nevşehir city center. The sample was calculated as 1012 students. However, when some possible lost cases were considered, it was calculated as 2024 students. Data was collected with questionnaire that included questions about demographic characteristics, smoking, alcohol and substance use. Required consents were obtained. Results: The mean age of the students was ±16 and 57.9% of the participants were girl, 42.1% of them were boy. Also, of them; 13.3% smoked, 12.6% used alcohol, and 6.2% used substance. Students stated that of their parents; 48.9% smoked, 6.7% used alcohol and 4.6% used substance and also 33.8 % didn’t use harmful substance. Again, of the students; 41.6% smoked because of friends, 46.4% used alcohol to have fun, 47.6% used substance because of curiosity. Also, 73.4 % of them stated that “substance abuse is manageable”. Conclusion: It is seen that high school students in the study are risky group in terms of adolescent health. It is suggested that the studies focused on solution with cooperation with health professionals, family and school should be conducted.